A Coloration Biochip for Optical Virus Detection Based on Printed Single Nanoparticle Array. Issue 10 (3rd February 2022) - Wang, Huadong; Zhang, Zeying; Su, Meng; Sun, Yali; Mikhailova, Julia V.; Cai, Zheren; Wu, Dongdong; Wang, Keyu; Pan, Qi; Chen, Bingda; Zuev, Dmitry; Song, Yanlin
Abstract: Direct and ultrasensitive detection of nanoscale objects is of great importance for materials science and biomedical application. Here, a printed single nanoparticle array‐based coloration biochip is developed for direct visualizing nanoscale objects with the microscopy image. Arising from the scattering cross section induced Mie scattering enhancement, the color change of nanoparticles with/without viruses can be observed with a conventional optical microscope. The scattering light from single nanoparticle has the size‐dependent characteristics of wavelength and intensity variation, allowing for optically detecting nanoscale virus. By comparing optical images before and after attaching viruses, quantitative detection can be achieved with the virus concentrations from 1.0 × 10 2 to 1.0 × 10 6  PFU mL –1 and a detection limit of 1.0 × 10 2  PFU mL –1 . The antibody‐modified array can specifically recognize influenza viruses in 15 min. The result provides a promising approach to detect diverse biological samples, including protein, exosomes, and platelet microparticle. Abstract : Viruses recognized by printed single nanoparticle array display the size‐dependent scattering characteristics of peak wavelength and intensity variation, which shows the characteristic spectra and optical images for identifying viruses. Direct visualizing nanoscale objects is achieved on the microscopy image for early‐stage disease diagnosis and environmental monitoring.